Instrumental Mentoring for Young Adults: A Multi-Method Study. Issue 4 (July 2021) - Schenk, Loïs; Sentse, Miranda; Lenkens, Margriet; Nagelhout, Gera E.; Engbersen, Godfried; Severiens, Sabine
Closeness between mentor and mentee is previously defined as an important indicator of relationship quality in youth mentoring, but whether this is the case in instrumental mentoring for young adults remains unclear. This is an exploratory study examining how instrumental mentoring serves young adults in their instrumental needs and how relational closeness develops. We applied a mixed-methods design, using quantitative data from a study of an instrumental mentoring program in Rotterdam, The Netherlands ( N = 53), and qualitative data from a subsample of participants ( N = 10). Two statistically distinctive clusters of closeness were found; 49% of the mentees reported high levels of closeness, and 51% reported low levels of closeness in their mentor relationship. Multivariate analyses of variance (MANOVAs) showed that the cluster with high levels of closeness was correlated with instrumental compatibility, satisfaction, and perceived attitude similarities. Semi-structured interviews were used to illustrate the role and development of closeness for mentees in both clusters, and three cases were presented. Experiencing closeness seemed a result of receiving instrumental support, not a precondition. Mentees' previous experiences might in some cases explain the lower levels of closeness, but this did not always hinder mentees to profit from their mentors' support.